ADAB SISWA TERHADAP GURU MENURUT PANDANGAN SAYYID MUHAMMAD NAQUIB AL-‘ATTHAS DALAM MENJAWAB TANTANGAN REVOLUSI INDUSTRI 4.0 - Saleh, Fauzi Ansori; Muqowim, Muqowim; Radjasa, Radjasa (Jurnal Tawadhu, 2020)
The value of a person's personality is measured by the attitudes and actions taken. Good attitude and actions will bring someone to a noble degree. But in the era of the industrial revolution 4.0, positive attitudes and behaviors that reflect the noble manners of a person are eroded by the disruption effect of the industrial revolution 4.0. This shift in mindset and patterns of social relations in the era of the industrial revolution 4.0 also touched the realm of education. The number of student behaviors that lead to the deterioration of etiquette is a concern for all circles. Especially bad manners are actually carried out by students to their own teacher.Sayyid Muhammad Naquib al-tAtthas as a Muslim scholar and thinker offered an educational concept known as ta'dib. Through the concept of ta'dib, education is projected as a process of forging reason, growth of character and character of students. With the concept of ta'dib, various negative student behaviors as an effect of disruption of the industrial revolution 4.0 can be placed in proportion to then look for formulas to answer the challenges that arise as a result of progress.